Pest categorisation of naturally‐spreading psorosis. (30th November 2017) - ,; Jeger, Michael; Bragard, Claude; Caffier, David; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Gregoire, Jean‐Claude; Jaques Miret, Josep Anton; MacLeod, Alan; Navajas Navarro, Maria; Niere, Björn; Parnell, Stephen; et al.
Abstract: The EFSA Panel on Plant Health performed a pest categorisation of naturally‐spreading psorosis of citrus for the European Union. Naturally‐spreading psorosis is poorly defined, because the status of both the disease and its causal agent(s) is uncertain. However, Citrus psorosis virus (CPsV) is a well‐ characterised Ophiovirus that is systematically associated with the psorosis disease and therefore considered to be its causal agent. Efficient diagnostics are available for CPsV. It is present in at least three EU MS. Naturally‐spreading psorosis is currently regulated by Directive 2000/29/EC, while CPsV is not explicitly mentioned in this Directive. CPsV has the potential to enter, establish and spread in the EU territory. However, the main pathway for entry is closed by the existing legislation so that entry is only possible through minor alternative pathways. Plants for planting are the major means of spread while there are uncertainties on the existence and efficiency of a natural spread mechanism. CPsV introduction and spread in the EU would have negative consequences on the EU citrus industry. Of the criteria evaluated by EFSA to qualify as a Union quarantine pest or as a Union regulated non‐quarantine pest (RNQP), Naturally‐spreading psorosis does not meet the criterion of being a well characterised pest or disease. As it is not explicitly mentioned in the legislation, it is unclear whether CPsV meets the criterion of being currently regulated or under official control. It meets, however, all the RNQP criteria. The key uncertainties of this categorisation concern: (1) the causal role of CPsV in the psorosis disease as well as elements of its biology and epidemiology, (2) the exact nature of the Naturally‐spreading psorosis syndrome and the identity of its causal agent and, consequently, (3) whether CPsV should be considered as being covered by the current legislation.